2019
DOI: 10.1002/eco.2132
|View full text |Cite
|
Sign up to set email alerts
|

Tree density influences ecohydrological drivers of plant–water relations in a larch boreal forest in Siberia

Abstract: Transpiration and stomatal conductance in deciduous needleleaf boreal forests of northern Siberia can be highly sensitive to water stress, permafrost thaw, and atmospheric dryness. Additionally, north‐eastern Siberian boreal forests are fire‐driven, and larch (Larix spp.) are the sole tree species. We examined differences in tree water use, stand characteristics, and stomatal responses to environmental drivers between high and low tree density stands that burned 76 years ago in north‐eastern Siberia. Our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…We observed that roots excised from the organic horizon were most active in N uptake. This supports findings from nearby stands that demonstrated that larch water uptake was from shallow sources associated with precipitation more so than deep water sources associated with thawing permafrost (Kropp et al, 2019). Analysis of the root traits of a congeneric, L. decidua , revealed that larch have a conservative rather than acquisitive strategy, for example, high diameter, low specific root length and high tissue density (Liese et al, 2017) similar to other conifers (Withington et al, 2006).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We observed that roots excised from the organic horizon were most active in N uptake. This supports findings from nearby stands that demonstrated that larch water uptake was from shallow sources associated with precipitation more so than deep water sources associated with thawing permafrost (Kropp et al, 2019). Analysis of the root traits of a congeneric, L. decidua , revealed that larch have a conservative rather than acquisitive strategy, for example, high diameter, low specific root length and high tissue density (Liese et al, 2017) similar to other conifers (Withington et al, 2006).…”
Section: Discussionsupporting
confidence: 87%
“…To assess relationships between tree density and characteristics of larch roots and root-associated fungi important to N acquisition, we intensively sampled 10 of 26 larch stands across a tree density gradient where tree productivity (Walker et al, 2021), understorey composition (Paulson et al, 2021) and ecohydrology (Kropp et al, 2019) have been described. Tree densities at the 10 stands (each stand ~0.5 ha, distance between stands 0.1 and 3.0 km) ranged from 0.10 to 3.70 trees/m 2 representing the range of densities that occur across the full density gradient (0.03 to 3.70 trees/m 2 ).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Our findings suggest a trend towards higher simulated VPD (almost 10%) across the entire period (516-2004 CE) compared to the global average of 1% 14 . The drastic thawing of permafrost in the subarctic forest and reduction of precipitation with increasing evaporative demand 4,13,44 could increase the risk of forest decline and mortality at these sites in the (near) future.…”
Section: Discussionmentioning
confidence: 99%
“…Precipitation and permafrost-thawed water during the summer are crucial for trees growing in regions with severe temperature limitations and predominantly continental climate conditions 1 4 . Although precipitation is low in the Siberian North, due to low temperatures, water loss is not yet as large as observed in European forest ecosystems 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, forest impacts on surface energy exchange exert a series of interrelated controls on permafrost and snow thermal dynamics (Loranty et al, 2018;Stuenzi et al, 2021). Variation in forest recovery within a single fire perimeter near Cherskiy has resulted in even-aged stands with canopy cover ranging from ∼10-95% (Paulson et al, 2021), and winter albedos of ∼0.3 and ∼0.7 at representative highand low-density stands (Kropp and Loranty, 2018;Kropp et al, 2019). Corresponding to post-fire tree density, summer and winter soil temperatures are warmer at sites with lower tree cover (Figure 1B) as a result of lower canopy shading and insulation from organic soils, and snow redistribution, respectively.…”
Section: Discussion Of Emerging Ecosystem Changes With Implications For Cryospheric Climate Feedbacksmentioning
confidence: 99%